Governance and inclusive food systems: Highlights from SHiFT Work Package 3 - CGIAR (CGIAR, 2024)
Political, social, and economic forces are interwoven throughout food value chains, hindering progress toward sustainable healthy diets. Untangling these webs of actors, forms of powers, and structures is key for achieving transformative change. Learn how the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT)is exploring the political economy of food systems in this video featuring Chris Béné, SHiFTWork Package 3 Lead, and Abdul-Rahim Abdulai, SHiFT Postdoctoral Fellow.